CONSTRUCTION AND EXPRESSION OF THE REPLICATIONDEFICIENT ADENONIRUS VECTOR OF HUMAN GM-CSF* - Zhang, Weiping; Cao, Xueta; Tao, Qun; Hamada, Hirofumi (Chinese Journal of Cancer Research, 2013)
The full-length cDNA encoding human Granuiocyte-macrophage colony-stimulating factor (GMCSF) was cloned by RT-PCR, placed under the control of CMV promoter, and inserted into adenovirus vector of El-substitution type, pAxlcw. Subsequently, the cassette cosmid was cotransfected into 293 cells together with EcoT22I-digested Ad5-TPC, and the replication-deficient recombinant adenoviruses(Ad) of human GM-CSF were generated efficiently by homologous recombination, with the titers of 1.51×109pfu/ml. 48 hours after infection with prepared human GM-CSF recombinant adenoviruses in vitro, HeLa cells and primary human skin fibroblasts expressed high levels of human GM-CSF (80~400ng/106cells/24hr). These suggest that the recombinant Ad of human GM-CSF prepared by COS/TPC method is effective in mediating GM-CSF gene transfer and might be used in cancer gene therapy.